Utilização de recursos de compensação reativa de indústrias no controle de tensão de sistemas elétricos - Warney Araujo Silva (2007)
A complex set of activities is required to assure that Power Systems are able to supply energy with high quality and reliability level. These activities are related to Expansion and Operation tasks, including from planning studies to real time control. Regarding control activities, the voltage control of system busbars is one of the most relevant. In fact, this activity must be considered in a reactive power control context, allowing addressing not only the aim of keeping voltage amplitude in a recommended band, but also the reactive power flow optimization. Shunt capacitor banks are one of the most used voltage control equipment. Their application constitutes the main focus of this work that presents a proposal for the use of the reactive power sources located in industries to promote better system voltage control. This thesis has a relevant result: using the idle shunt capacitor banks installed in industries, during the period when the system is subjected to higher power demand, may lead to a significant gain, in terms of technical and economical aspects.